2013
DOI: 10.1007/s12032-013-0681-x
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of microRNA-203 is associated with advanced tumor progression and poor prognosis in epithelial ovarian cancer

Abstract: MicroRNA-203 (miR-203), possessing tumor suppressive or promotive activities, has been found to be downregulated or upregulated in different cancer types. The purpose of this study was to investigate whether the increased expression of miR-203 can be used as a noninvasive diagnostic and prognostic biomarker in epithelial ovarian cancer (EOC). Real-time quantitative PCR was performed to detect the expression levels of miR-203 in EOC tissues. The expression levels of miR-203 were significantly higher in EOC tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 23 publications
4
30
0
1
Order By: Relevance
“…Whether miRNAs act as oncogenes or tumor suppressor genes depends on the context. For example, miR-203 behaves as a tumor suppressor and is downregulated in pancreatic, glioma and esophageal cancer, while it is upregulated in epithelial ovarian cancer and acts as an oncogene (9,(20)(21)(22). The present study demonstrated that miR-203 was downregulated in NSCLC specimens, which is in agreement with a …”
Section: Discussionsupporting
confidence: 90%
“…Whether miRNAs act as oncogenes or tumor suppressor genes depends on the context. For example, miR-203 behaves as a tumor suppressor and is downregulated in pancreatic, glioma and esophageal cancer, while it is upregulated in epithelial ovarian cancer and acts as an oncogene (9,(20)(21)(22). The present study demonstrated that miR-203 was downregulated in NSCLC specimens, which is in agreement with a …”
Section: Discussionsupporting
confidence: 90%
“…For instance, Pecot et al reported that miR-200 inhibited angiogenesis and induced vascular normalization in several tumors through direct and indirect mechanisms partially via targeting interleukin-8 [12]. Wang et al showed that elevation of miR-203 was associated with advanced progression and poor prognosis in EOC [13].…”
Section: Discussionmentioning
confidence: 99%
“…There were 24 articles including 27 studies that reported data about tissue miR-203 expression and the prognosis, which involved 2,408 cancer patients [13, 15-23, 26-31]. Since the result of meta-analysis exhibited obvious heterogeneity ( P <0.001, I 2 =88.3%) (Table 2), we used a random model to calculate the pooled HR and 95% CI from the 22 studies that provided OS of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, miR-203 is involved in tumor cell differentiation, proliferation and metastasis, and is thought to be a tumor suppressor. However, upregulation of miR-203 has been found in multiple tumor types including colorectal cancer [26, 32, 36], pancreatic cancer [34, 35, 37], renal cell carcinoma [28], breast cancer [25, 33] and ovarian cancer [31], indicating that miR-203 may also exhibit oncogenic potential, likely due to its ability to induce MET and promote metastatic colonization at distant sites [26]. Thus, it is controversial that whether miR-203 expression can be used as a prognostic biomarker in cancer.…”
Section: Discussionmentioning
confidence: 99%